IDENTIFIKASI IBU HAMIL YANG MELAKUKAN KUNJUNGAN ANTENATAL CARE DI WILAYAH KERJA PUSKESMAS WAPUNTO KABUPATEN MUNA - Wa ode Sitti Asma (JURNAL ILMIAH KESEHATAN MASYARAKAT DAN SOSIAL, 2023)
Antenatal care is a health service by professionals for mothers during their pregnancy which is carried out in accordance with established antenatal service standards. Wapunto Health Center is one of the health facilities in Duruka District that has a low Antenatal Care Visit at 48.8%. This has not yet reached the national targets set, namely for K1 (100%) and K4 (95%) coverage (Permenkes RI, 2014). This research is a descriptive research with a quantitative approach. Researchers measured age, parity, education level, knowledge and family support for antenatal care visits. The number of respondents as many as 30 people with sampling was selected using the nonprobably sampling method with accidental sampling technique. Research Instrument with Questionnaire. The results of the study found that ANC visits were incomplete from 30 respondents, namely mothers aged <20 and >30 years as many as 10 people (83.3%), mothers with multiparity as many as 11 people (52.4%), mothers with secondary education level as many as 15 people (83.3%), mothers with less knowledge as many as 9 people, and mothers with sufficient family support as many as 11 people. Puskesmas need to increase promotional efforts such as counseling activities on the importance of pregnancy checks or ANC.